Phytochemical Profile and Antioxidant Activity of Torch Ginger Flower Tea at Various Drying Temperatures - Yusnita Wahyuni Silitonga; Rafiqah Amanda Lubis; Nurmaini Ginting; Fatma Suryani Harahap; Muhammad Nizar Hanafiah Nasution; Muttaqin Kholis Ali (Postgraduate, University of Mataram, 2026)
Kecombrang can be categorized as a functional plant because it contains phytochemical compounds and antioxidants that can be further developed into herbal tea products. The objective of this study was to determine the phytochemical constituents and antioxidant activity of kecombrang tea processed at three different drying temperatures: 60, 70, and 80 °C. Phytochemical profiling was conducted using both qualitative and quantitative approaches. The qualitative analysis included the identification of alkaloids, flavonoids, tannins, saponins, steroids, glycosides, and triterpenoids, while the quantitative analysis focused on total flavonoids and total phenolics. The results revealed that all tested phytochemical compounds were present in the kecombrang tea extracts except saponins. The highest total flavonoid content was observed at the drying temperature of 60 °C, reaching 32.21 mg QE/g extract, whereas the lowest was recorded at 80 °C with 8.61 mg QE/g extract. Interestingly, the extract processed at 80 °C exhibited the highest total phenolic content at 11.60 mg GAE/g extract, while the lowest phenolic content was found at 60 °C with 2.72 mg GAE/g extract. The strongest antioxidant activity was also observed at 80 °C, with an IC50 value of 34.92 ppm. Overall, increasing the drying temperature tended to decrease most phytochemical constituents.